Broadband Koch Fractal Boundary Printed Slot Antenna for ISM Band Applications - Reddy, V. V. (Advanced Electromagnetics, 2018)
A new broadband radiating slot antenna with fractal shape is modeled, fabricated and experimentally studied. The presented slot antenna is examined for first three iterations. Optimization of iteration factor (IF) and iteration angle (IA) have been done for each iteration order (IO) to enhance impedance bandwidth significantly. All the antennas are fed with a simple microstrip line. Bandwidth achieved with Antenna 1 (IO=1, IF=0.35 and IA=600) is 1550 MHz which is five times more than that of the square slot antenna. The performance of the proposed fractal slots is also compared with the rotated slot antenna. The experimental data validates the reported analysis with a close agreement.